1992
DOI: 10.1073/pnas.89.6.2434
|View full text |Cite
|
Sign up to set email alerts
|

Participation of bacteriorhodopsin active-site lysine backbone in vibrations associated with retinal photochemistry.

Abstract: Bacteriorhodopsin (bR) has been biosynthetically prepared with lysine deuterated at its a carbon (Ca-H). The labeled membranes containing bR were investigated by difference Fourier transform infrared (FTIR) spectroscopy. It has been derived from K/bR and M/bR difference spectra (K and M are photocycle intermediates) that several bands previously assigned to the retinal chromophore are coupled to the Ca-H. The vibrational modes that exhibit this coupling are principally associated with C15-H and N-H vibrations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 18 publications
(18 reference statements)
2
30
0
Order By: Relevance
“…Previous papers (4143) have suggested that the C—C and C—N stretching vibrations of the side chain of Lys216 contribute to vibration bands in the 1150-1030 cm −1 region. The present results also suggest that these vibrational bands are further coupled with the retinal C 15 —H bending vibrations.…”
Section: Resultsmentioning
confidence: 94%
“…Previous papers (4143) have suggested that the C—C and C—N stretching vibrations of the side chain of Lys216 contribute to vibration bands in the 1150-1030 cm −1 region. The present results also suggest that these vibrational bands are further coupled with the retinal C 15 —H bending vibrations.…”
Section: Resultsmentioning
confidence: 94%
“…6.IOS Evidence for secondary a-helical structural changes in the protein at the M and N stages is provided by changes in the FTIR amide bands;IIO.112 by X-ray, electron, and neutron diffraction; 113-116 by spin label techniques:" and by changes in the backbone of Lys-216. 118 Mechanistically, it has been argued that the protein structural change is associated directly with the 13-cis configuration assumed by the chromophore during the photocycle-!" or by the deprotonated state of the Schiff base at the M stage."…”
mentioning
confidence: 99%
“…The intermediates are commonly represented by a single letter code where the index represents the absorption maximum [13]. When exposed to light at 568 nm, the molecules in the initial state (bR 568 ) convert to the short-living J 625 and proceed to the K 590 state [14][15][16]. During these initial steps, the isomerization from all-trans to 13-cis retinal occurs.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The proton pumping of this protein is coupled with photochemical conversions, occurring during a photocycle of bR [13][14][15][16][17][18]. The…”
Section: Introductionmentioning
confidence: 99%